2004
DOI: 10.2111/1551-5028(2004)057[0583:iawrao]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Among Western Ragweed and Other Sandhills Species After Drought

Abstract: Interannual differences in yield and species composition of herbaceous vegetation on semiarid rangelands are common and often related to variations in precipitation regime. Interspecific interactions that occur after drought-induced population fluxes of western ragweed (Ambrosia psilostachya D.C.) were evaluated by removing western ragweed or associated species from 1-m 2 quadrats at weekly intervals beginning in early May, June, or July 1991 or 1992 on high-seral sandhills prairie in Nebraska. The composite o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Vermeire and Gillen (2000) reported standing crops of western ragweed at 600 kg ha À1 can be tolerated before control should be considered. However, Reece et al (2004) reported that seasonal grass production on the sandhills prairie was reduced 21% when western ragweed herbage levels of 189 kg ha À1 were present following dry weather in the spring.…”
mentioning
confidence: 99%
“…Vermeire and Gillen (2000) reported standing crops of western ragweed at 600 kg ha À1 can be tolerated before control should be considered. However, Reece et al (2004) reported that seasonal grass production on the sandhills prairie was reduced 21% when western ragweed herbage levels of 189 kg ha À1 were present following dry weather in the spring.…”
mentioning
confidence: 99%